Monitoring of organochlorine pesticide and polychlorinated biphenyl residues in common swifts (Apus apus) in the region of Hannover, Lower Saxony, Germany - Tiyawattanaroj, Warakorn; Witte, Stefan; Fehr, Michael; Legler, Marko (Veterinary Sciences, 2021)
The use of pesticides is associated with the decline of several avian species. In this study, we monitored the organochlorine contaminants in common swifts (Apus apus) in the years 2016 to 2018. These long-distance migrants breed in Europe and winter in Africa. Their only feeding source is aerial plankton. Pooled organ samples of 42 adult and 40 juvenile swifts were tested with the multi-residue method by gas chromatography-mass spectrometry (GC-TOF/MS). Predominantly, 4,4′-DDE, dieldrin, hexachlorobenzene (HCB), lindane and polychlorinated biphenyls (PCBs) were found in most of these common swifts. Only 4,4′-DDE (adult: 83 ± 70 μg/kg, juvenile: 17 ± 39 μg/kg) and dieldrin (adult: 2 ± 3 μg/kg, juvenile: 0.3 ± 1 μg/kg) concentrations were significantly different between adult and juvenile birds. All detected concentrations in our study were far lower than the previously recorded pesticide concentrations of common swifts in Italy and those which are known to cause toxicity and death in birds.